2001
DOI: 10.1079/phn2001162
|View full text |Cite
|
Sign up to set email alerts
|

The school setting: an opportunity for the implementation of dietary guidelines

Abstract: Nutrition, physical activity and health related promotion programmes in schools have developed into a mature field of research over the past decades. A number of success factors have been identified and evidence-based interventions have been performed. However, the school setting as an arena for evidence-based health promotion programmes, is still not used to its full potential. Schools provide an excellent arena for reaching large segments of the population, such as young people, school staff, families and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
(25 reference statements)
0
30
0
3
Order By: Relevance
“…O envolvimento dos pais nesse processo educativo dá a eles a oportunidade de se tornarem modelos apropriados para os filhos, assumindo um papel fundamental na construção dos hábitos alimentares das crianças. Por fim, o fornecimento ininterrupto de frutas e verduras nas escolas possibilita que as crianças e os adolescentes tenham acesso a esses alimentos, tornando viável a sua incorporação nos hábitos alimentares das crianças [44][45][46] .…”
Section: Discussionunclassified
“…O envolvimento dos pais nesse processo educativo dá a eles a oportunidade de se tornarem modelos apropriados para os filhos, assumindo um papel fundamental na construção dos hábitos alimentares das crianças. Por fim, o fornecimento ininterrupto de frutas e verduras nas escolas possibilita que as crianças e os adolescentes tenham acesso a esses alimentos, tornando viável a sua incorporação nos hábitos alimentares das crianças [44][45][46] .…”
Section: Discussionunclassified
“…10 In South Africa, since the development of the FBDG, several school-based initiatives have used these guidelines to develop nutrition education materials to complement the national curriculum on nutrition. 11 However, these programmes were only experimental and very few educators indicated that they use these materials to teach nutrition at schools.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, school meals should be part of the educational process to teach students healthy food choices and promote good eating habits. [27][28][29] However, the results of the current study presented some problems and showed an urgent need for improvements related to school meal programs from an educational perspective. As a result of evaluating the achievement level of educational school meal programs, the total average score did not even reach to 50 out of 100, with significant differences among school levels.…”
Section: Discussionmentioning
confidence: 76%
“…School-based nutrition education should focus not only on the provision of nutrition information, but also on the development of skills and behaviors related to areas such as experiential activities like cooking class, school gardening, and exhibitions. 27,33,34 Experiential nutrition education improved cognitive behaviors that may mediate healthy food choices. 35 In our study, the cooking class score was only 3.5 out of 10.…”
Section: Discussionmentioning
confidence: 99%